2013
DOI: 10.1002/ajmg.a.35706
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mortality and causes of death in the Swedish Down syndrome population

Abstract: During the past few decades age at death for individuals with Down syndrome (DS) has increased dramatically. The birth frequency of infants with DS has long been constant in Sweden. Thus, the prevalence of DS in the population is increasing. The aim of the present study was to analyze mortality and causes of death in individuals with DS during the period 1969-2003. All individuals with DS that died between 1969 and 2003 in Sweden, and all individuals born with DS in Sweden between 1974 and 2003 were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
154
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(163 citation statements)
references
References 31 publications
9
154
0
Order By: Relevance
“…Respiratory disease accounts for 43-78% of intensive care unit admissions, and 50% of those required ventilation support [12,36,37]. Respiratory illness is second only to CHD in mortality of individuals with Down syndrome at any age [38]. The average hospital stay due to lower respiratory illness is longer for children with Down syndrome [11].…”
Section: Respiratory Disease In Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory disease accounts for 43-78% of intensive care unit admissions, and 50% of those required ventilation support [12,36,37]. Respiratory illness is second only to CHD in mortality of individuals with Down syndrome at any age [38]. The average hospital stay due to lower respiratory illness is longer for children with Down syndrome [11].…”
Section: Respiratory Disease In Down Syndromementioning
confidence: 99%
“…For persons with Down syndrome aged <3 years, respiratory illnesses are the most common cause of hospital admissions [165], and respiratory disease is by far the most common cause of death in persons with Down syndrome [38]. Both intrinsic immune defects and extrinsic (anatomical) factors contribute to disturbed immune function and respiratory infection in individuals with Down syndrome [166][167][168].…”
Section: Immune System Disturbances Impacting Cardiopulmonary Functiomentioning
confidence: 99%
“…3,6 Approximately half of infants with Down syndrome are diagnosed with congenital heart defects, compared with a baseline risk of ∼1%. 7,8 Related complications, such as pulmonary hypertension and heart failure may affect health and survival, 9 but a change in attitudes toward treatment of infants with Down syndrome, corrective heart surgery included, has improved prognosis. 10,11 For example, the infant mortality rate among infants with Down syndrome in Sweden has decreased from 41% during 1969 to 1973 to 4% during 1999 to 2003.…”
mentioning
confidence: 99%
“…10,11 For example, the infant mortality rate among infants with Down syndrome in Sweden has decreased from 41% during 1969 to 1973 to 4% during 1999 to 2003. 9 Recent studies from Norway and Canada have demonstrated small declines in the incidence of congenital heart defects over time in the general population. 7,12 Improved diagnostic tools like fetal echocardiography may have led to more pregnancy terminations when severe malformations are diagnosed antenatally.…”
mentioning
confidence: 99%
“…While the hematological abnormalities observed in newborns and infants with DS vary case by case, the following abnormalities are often observed: macrocytosis, neutrophilia, thrombocytopenia, and polycythemia [28][29][30]. In contrast to the high risk of leukemias in the pediatric period, leukemias are no longer a common cause of death in adults with DS [31]. Instead, macrocytosis and leucopenia are often observed in adult DS cases, leading to the early onset of myelodysplastic syndrome and bone marrow failure [32].…”
Section: Hematopoiesis In Down Syndromementioning
confidence: 99%